CFD prediction of shell-side flow and mass transfer in regular fiber arrays. (April 2021) - Cancilla, N.; Gurreri, L.; Marotta, G.; Ciofalo, M.; Cipollina, A.; Tamburini, A.; Micale, G.
Highlights: Hexagonal and square lattices under steady-state, fully developed conditions. Axial flow: fz and Sh increase by 26% and 79% in the hexagonal lattice. Transverse flow: fT increases by 10-36% in the hexagonal lattice; similar Sh values. Mixed flow: fT unaffected by axial flow; fz increased at transverse Re>~5-10. Sh is the larger between that of purely transverse flow and purely axial flow. Abstract: Numerical simulations were conducted for fully developed, steady-state flow with mass transfer in fiber bundles arranged in regular lattices. The porosity was 0.5 and the Schmidt number 500. Several combinations of axial flow, transverse flow and flow attack angles in the cross-section plane were considered. The axial and transverse Reynolds numbers Re z, Re T were made to vary from 10 −4 to 10 2 . Concentration boundary conditions, and the definition of an average Sherwood number, were addressed. Results for the hydraulic permeability were compared with the literature. Both hexagonal and square lattices were found to be hydraulically almost isotropic up to transverse flow Reynolds numbers Re T of ~10, while they behaved anisotropically in regard to mass transfer even at Re T as low as 0.1. A larger anisotropy was exhibited by the square lattice. In mixed (axial+transverse) flow, the transverse friction coefficient was almost completely unaffected by the simultaneous presence of axial flow, while the axial friction coefficient (and thus the axial pressure loss) increased with the transverse Reynolds number for Re T >~5-10. In regard to mass transfer, the Sherwood number settled in all cases to the higher between the Sherwood number in purely transverse flow and that in purely axial flow. Graphical abstract: Image, graphical abstract